Insulin pump therapy. Issue 4 (April 2021) - Peters, Catherine J.; Annan, Francesca; Hindmarsh, Peter C.; Thompson, Rebecca J.
Abstract: Intensive insulin therapy is the mainstay of diabetes care as it prevents or delays the long term complications of Type 1 diabetes mellitus. Insulin pump therapy can deliver improved diabetes control and at the same time reduce the number and serious nature of any hypoglycaemic episodes. The therapy is not associated with an increased risk of diabetic ketoacidosis. Pump therapy should follow National Institute for Health and Care Excellence Guidelines and be instigated and supported by teams experienced in insulin pump therapy, with skills and competences to ensure sustained positive outcomes. Continuous glucose monitoring further improves blood glucose control providing continuous feedback with warnings of rapid changes in glucose and/or attainment of high or low glucose concentrations. Continuous glucose monitoring is cost effective by reducing fear of hypoglycaemia, blood glucose finger prick testing and a marked reduction in hypoglycaemic episodes. The hybrid closed loop systems offering algorithm driven insulin adjustment based on sensor readings are now commercially available bringing into play more effective and safer insulin delivery with a further step change in diabetes control and well being.